TEACHING FACTORY DALAM MENGHASILKAN LULUSAN SIAP BEKERJA DAN BERWIRAUSAHA - Sugianto Sugianto; Casmudi Casmudi (STKIP Persada Khatulistiwa Sintang, 2022)
This research is motivated by the low ability of students who are ready to work and ready to be entrepreneurs. The purpose of this study is to describe the school's efforts in preparing graduates who are ready to work and ready for entrepreneurship through the Teaching Factory (TEFA) model learning. This research method uses a qualitative case study approach. Data collection was done by interview and observation. Interviews were conducted by means of FGDs with selected resource persons according to their roles and functions, while observations were carried out in class. The results showed that schools made efforts to apply for the Vocational Center of Excellence (VCE) program through the Directorate of Vocational Education at the Ministry of Education and Culture. The success of achieving the PK-SMK program was continued in collaboration with the retail company Alfamidi, the East Kalimantan Province branch. Implementation of learning with an integrated school curriculum with Industry and Work World Industry (IDUKA). The obstacles to implementing TEFA are psychological barriers for teachers who feel that their role has been reduced. Alignment of competency standards with IDUKA. Implementing teacher internships in overcoming barriers to an integrated curriculum and presenting guest teachers in classes from IDUKA.